2017
DOI: 10.1016/j.vph.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin-induced arterial contraction is Gi- and calcium-dependent

Abstract: Chemerin is an adipokine associated with increased blood pressure, and may link obesity with hypertension. We tested the hypothesis that chemerin-induced contraction of the vasculature occurs via calcium flux in smooth muscle cells. Isometric contraction of rat aortic rings was performed in parallel with calcium kinetics of rat aortic smooth muscle cells to assess the possible signaling pathway. Chemerin-9 (nonapeptide of the chemerin S157 isoform) caused a concentration-dependent contraction of isolated aorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…5A) demonstrates that chemerin still has a role to play in blood pressure regulation. This is in accordance with previous in vitro studies on blood vessel contractility (Watts et al, 2013;Ferland et al, 2017). A 7-mmHg fall in MAP with the whole-body chemerin ASO may seem modest, but this reproducible indication of blood pressure control by chemerin in a normal SD rat offers promise that continued study will demonstrate an interaction between chemerin and blood pressure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5A) demonstrates that chemerin still has a role to play in blood pressure regulation. This is in accordance with previous in vitro studies on blood vessel contractility (Watts et al, 2013;Ferland et al, 2017). A 7-mmHg fall in MAP with the whole-body chemerin ASO may seem modest, but this reproducible indication of blood pressure control by chemerin in a normal SD rat offers promise that continued study will demonstrate an interaction between chemerin and blood pressure.…”
Section: Discussionsupporting
confidence: 90%
“…The normal SMA also has the ability to contract in a chemerin receptor-dependent manner when stimulated with an electrical field, a contraction that was dependent on PVAT and the sympathetic nervous system (Darios et al, 2016). We have identified the mechanism of vascular contraction in normal animals as an operation through the smooth muscle cells themselves that works in a calcium-dependent manner (Ferland et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this latter study also demonstrated chemerin receptor‐dependent contraction of RTA by chemerin‐9, a nonapeptide derived from chemerin (Wittamer et al, ). More recently, the same group demonstrated the Gαi dependence of this contraction, with downstream activation of both src and ρ kinase (Ferland et al, ). Whilst this may seem contradictory to the findings in this study, the activation of the same GPCR to generate opposing effects is demonstrated with the activation of FPR2 by both serum amyloid A and annexin A1 to give pro‐inflammatory and anti‐inflammatory actions.…”
Section: Discussionmentioning
confidence: 97%
“…Elevated levels of serum chemerin in patients with OSA can abolish the function and inhibit the formation of the vascular endothelium, thereby promoting the occurrence and development of hypertension [110]. Further research has found that increased expression of chemerin and CMKLR1 may activate the ROCK2/P-MYPT1 pathway, which is one of the classical MLC phosphorylation-dependent pathways, thereby inducing the contraction of vascular smooth muscle cells (VSMC) [111] or the activation of the L-type Ca2+ channel through the Gi protein, causing calcium-dependent calcium influx in VSMC [112]; additionally, chemerin can stimulate aortic smooth muscle cell proliferation via autophagy, which leads to vascular remodeling in metabolic hypertension [113].…”
Section: Cvdsmentioning
confidence: 99%